2005
DOI: 10.1055/s-2005-836776
|View full text |Cite
|
Sign up to set email alerts
|

Klinisches Outcome nach Roboter-assistierter versus konventionell implantierter Hüftendoprothetik: Prospektive, kontrollierte Untersuchung von 71 Patienten

Abstract: The significant functional impairment following robotic assisted THA should be taken critically into consideration prior to initiating such procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(20 citation statements)
references
References 18 publications
0
19
0
1
Order By: Relevance
“…The same study 12 reported that two patients who underwent robotic-assisted THA (6%) and one who underwent conventional THA (3%) required revision surgery. None of the patients in any other studies, however, required revision.…”
Section: Surgical Aspectsmentioning
confidence: 79%
See 1 more Smart Citation
“…The same study 12 reported that two patients who underwent robotic-assisted THA (6%) and one who underwent conventional THA (3%) required revision surgery. None of the patients in any other studies, however, required revision.…”
Section: Surgical Aspectsmentioning
confidence: 79%
“…For example, rates of thigh pain after 1, 3 and 12 months were similar in patients who underwent robotic-assisted and those who underwent conventional THA. 9 10 Although one study 12 found that the rate of Trendelenburg signs was significantly higher in the robotic-assisted than in the conventional THA group (61% vs 26%, p=0.0014), this outcome was not measured in the other six included studies.…”
Section: Surgical Aspectsmentioning
confidence: 96%
“…Overall complications were compared in nine RCT [25, 26, 2830, 76, 106108] and 28 prospective [16, 17, 19, 20, 32, 3437, 39, 41, 43, 4547, 49, 6870, 9496, 109113] studies. From these studies, the overall complication rate was 11.6 % (515/4453) in the robotic arm compared with 21.4 % (693/3245) in the open arm.…”
Section: Resultsmentioning
confidence: 99%
“…Analysis of the 76 prospective studies revealed that just 47 [1620, 23, 3137, 39, 41, 43, 47, 49, 55, 57, 59, 61, 64, 65, 6771, 75, 85, 86, 88, 89, 91, 9496, 101, 111113] of them (61.8 %) had adequate power for outcome evaluation, assuming large effect sizes. For medium effect sizes, 20 studies [3133, 3537, 41, 43, 59, 61, 6770, 75, 85, 86, 95, 111, 112] (26·3 %) were sufficiently powered.…”
Section: Resultsmentioning
confidence: 99%
“…Other surgical complications they reported were insertion of the cup at a suboptimal angle needing revision, femoral fissuring during repositioning and excess blood loss. Siebel and Käfer using the CASPAR system for hip arthroplasty reported a higher surgical time and an increased incidence of poor post op hip abductor function and incidence of Trendelenburg’s sign [33]. Similar technical and surgical complications have been reported with knee arthroplasty where procedures had to be abandoned due to failure of registration, robot workspace issues and damage to the patellar tendon [34, 35].…”
Section: Evidence For Robotsmentioning
confidence: 94%